Managers’ Attitudes Toward Codes of Ethics: Are There Gender Differences? - Ibrahim, Nabil (Journal of business ethics, 2009)
This article extends previous research by investigating the basis for attitudes toward codes of ethics. Specifically, its purposes are threefold. First, to examine business managers’ attitudes toward codes of ethics. Second, to ascertain whether gender differences do exist with respect to these attitudes. Third, to provide a benchmark for future studies of attitudes toward codes of ethics. A survey of 286 managers revealed significant differences between the female and male managers with respect to six of the eight variables studied.